2018
DOI: 10.3390/w10101369
|View full text |Cite
|
Sign up to set email alerts
|

Study on Risk Assessment and Early Warning of Flood-Affected Areas when a Dam Break Occurs in a Mountain River

Abstract: Under the influence of extreme weather conditions or other unfavorable factors, if a dam break occurs in a mountain river, it will cause a great number of casualties and property losses in the affected downstream areas. Usually, early warning of the affected areas downstream of the dam depends mainly on qualitative evaluation and cannot be quantitatively evaluated. Based on the authors’ calculation of floods for many years, this study presents a quantitative assessment method for flood risk. The Ertan Hydropow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…According to the FCEM, it is important to transform the interval value of a single evaluation indel into a certain value by using a membership function. The author constructed a membership function table for THSE assessment in JianYang County based on the characteristics of THSE and the research results of some other experts and scholars [59,60], as shown in Table 9.…”
Section: Evaluation Matrix Of Evaluation Indexesmentioning
confidence: 99%
“…According to the FCEM, it is important to transform the interval value of a single evaluation indel into a certain value by using a membership function. The author constructed a membership function table for THSE assessment in JianYang County based on the characteristics of THSE and the research results of some other experts and scholars [59,60], as shown in Table 9.…”
Section: Evaluation Matrix Of Evaluation Indexesmentioning
confidence: 99%
“…Furthermore, there is no widely accepted definition of the social impact of dam breaks. Therefore, the social impact of other industries or natural disasters and the existing research results of scholars can provide a reference for the establishment of a social impact assessment index system for dam breaks in this paper [57][58][59].…”
Section: Evaluation Index Systemmentioning
confidence: 99%
“…where ω is the weight of each evaluation index. Traditional set pair analysis defines the ratio of identity degree to opposite degree as set pair potential, as expressed in Equation (9).…”
Section: Determine the Connection Degreesmentioning
confidence: 99%
“…However, due to the storage of water on such a scale, huge potential energy is generated and poses a great threat to the downstream [2]. Dam break produces a large number of destructive floods [3][4][5][6], results in loss of life and economy [7][8][9], and causes enormous negative impact on the environment and ecosystem. In recent years, there have been many serious dam break accidents.…”
Section: Introductionmentioning
confidence: 99%